DESAIN PRIMER UNTUK AMPLIFIKASI REGIO PROMOTER GEN inhA ISOLAT P016 MULTIDRUG RESISTANCE Mycobacterium tuberculosis DENGAN METODE POLYMERASE CHAIN REACTION - Sari, Eka Nata (Jurnal Farmasi Udayana, 2018)
Mutations in the inh A promoter region are responsible for isoniazid resistance and cross-resistance to ethionamide. To identify mutations with polymerase chain reaction (PCR), a pair of primers that can amplify the target region. This aim of this study was to obtain the best primer pair to amplify the inh A promoter region  using the Clone Manager Suite 6 program. The inh A promoter sequence (Genbank: U66801) obtained from the www.ncbi.nlm.nih.gov was used as a template. The design results obtained the best primer pair tested in vitro using Polymerase Chain Reaction (PCR) method. The PCR amplification process was performed for 40 cycles with the following conditions: predenaturase (95 o C for 15 minutes), denaturation (94 o C for 1 minute), annealing (56 o C for 1 minute 30 seconds), elongation (72 o C for 2 minutes), and final elongation (72 o C for 10 minutes). Detection of PCR products was performed in agarose gel electrophoresis 1.3% w / v and visualized by UV transluminator tool. The results obtained were forward primers of 5'-GGTCGAAGTGTGCTGAGTC-3 'and reverse primer 5'-TGCTCTTCTACCGCCGTGA-3' which met the good primary criterion based on Clone Manager Suite 6. The pair of primers has been able to amplify the inh A promoter region by the length of product produced at 373 bp.